Peroneus Longus Tendoscopy at the Sole - Tun Hing Lui, M.B.B.S. (HK), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S.; Wilson Wai Shun Hau, M.B.Ch.B. (Arthroscopy Techniques, 2018)
Different pathologies can occur in the peroneus longus tendon at the sole. Many of them can be dealt with by peroneus longus tendoscopy of the sole. The purpose of this Technical Note is to describe the details of this minimally invasive approach to the peroneus longus tendon of the sole. This has the advantages of better cosmesis, less soft tissue dissection, less postoperative pain, and less peritendinous fibrosis.